Exploring the psychosocial implications on the management of adolescent Type 1 diabetes: A qualitative study involving healthcare providers, using in-depth interviews - Mashiane, Michelle (The IIE, 2020)
Chronic physical disorders, such as Type 1 diabetes, are conceptualised as an ongoing strain. Treatment methods include daily insulin administration, sticking to a healthy diet and exercise, as well as regular visitations to a diabetes healthcare team. Strand, Brostom and Haugstevedt (2016) argue that managing Type 1 diabetes may be especially demanding during adolescence, when various rapid cognitive, physical and social changes are taking place. The current study, thus, aimed to explore the psychosocial factors that influence the management of adolescent Type 1 diabetes in a South African context, from the perspectives of healthcare providers. Six participants were included using convenience sampling. The researcher embarked on this study from an interpretivist stance in terms of which a qualitative research strategy was employed. Semi-structured interviews were used to collect data in order to gain an in-depth understanding of the lived experiences of managing Type 1 diabetes as an adolescent. The results of this study revealed that various psychosocial factors act as risk and resistance factors to self-care behaviours. To be specific: the polarised healthcare system of South Africa, support structures, access to information, as well as the complexities of the adolescent developmental stage.
Keywords: Psychological effects; Type-1 diabetes; Adolescents; Management